ABOUT ISLAM POLITICIZATION IN THE CENTRAL ASIA: ESSENCE, THE REASONS, CONSEQUENCES - Abilekova, G. K. (Journal of Oriental Studies, 2016)
In present article the author defines the nature of Islam’s politicization, analyzes the reasons and consequences of this process interritory of the Central Asian countries. Dissolution of bipolar system of the world and discredit of dominating communistic ideologyare considered as the main stimulating factors of Islam’s politicization that has led «Islamic Renaissance» in this region. A negativeconsequence of Islam’s politicization was distribution of the extremist organizations of radical sense that threatens safety of the region’scountries.